Efficacy of Isothermic Conditioning over Military-Based Heat Acclimatization and Interval Training in Tropical Native Males - Tan, Shawn Chee Chong (LIPPINCOTT WILLIAMS & WILKINS, 2022)
10.1249/MSS.0000000000002991